The proPO and clotting system in crustaceans - Sritunyalucksana, Kallaya; Söderhäll, Kenneth (Aquaculture, 2000)
Research in the area of innate immunity in arthropods is rapidly progressing, whereas shrimp immunity research has been a subject of minor interest compared to similar research performed on other crustaceans and insects. Sritunyalucksana and Soderhall review what is known so far about crustacean defense mechanisms, particularly of penaeid shrimp, with special emphasis on the proPO and the clotting system.